TELAAH PEMIKIRAN KH. HASYIM ASY`ARI TENTANG KARAKTERISTIK PENDIDIKAN ISLAM - Fathorrozy Fathorrozy (LP2M IAI Miftahul Ulum Pamekasan, 2017)
Characteristic of Teachers in Islamic Education Assessing Research of KH. Mohammad Hasyim Asy’ari.The problems of study can be describe by the author, namely: First, how are the teacher’s characteristic in Islamic education according to KH. Mohammad Hasyim Asy’ari? Second, how are the ethics of teachers in Islamic education according to KH. Mohammad Hasyim Asy’ari? The author use library research, and qualitative approach. The data collected by using: Library research method, observation, and documentation, the data analyzed by interpretation and content analysis. According to the finding of this research, it can be concluded: according to KH. Mohammad Hasyim Asy’ari the teacher’s characteristic in Islamic education can be seen from the ethics that should be owned by a teacher. The ethics are: (a) Personally a teacher. Such as, always remember to Allah, wara’, tawaddhu’, zuhud, etc. (b) The teacher’s ethics in teaching. Such as, free from hadats and najis, read prayer, sitting in a place that can be seen by all of students, give chance to the students to ask, and set the schedule. (c) The teacher’s ethic to their students. Such as, accepting all kinds of students, no partial, low profile and humble to the all students, love the students and ask them to have a chat and soon.